Peningkatan Kesadaran Masyarakat terhadap Pencegahan Demam Berdarah Dengue melalui Pemanfaatan Minyak Jelantah menjadi Lilin Aromatherapy Lavender di Desa Krompaan - Ihza Zahral ‘Iffat; Azzahra Shafa Maulana; Wardani Oktavia; Ahmad Faiz (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Dengue Hemorrhagic Fever or known as DBD disease which is caused by a dengue virus caused by the Aedes Aegypti mosquito. The disease causes sufferers to experience severe pain, complications, and death. The UIN Walisongo KKN Team conducted community service activities in Krompaan Village with the aim of increasing public awareness and participation in preventing Dengue Hemorrhagic Fever (DBD). Considering that this village is located near a river, which has the potential to be a habitat for the Aedes Aegypti mosquito, effective prevention efforts are needed to prevent this disease, which is one of the infectious diseases that is still endemic in Indonesia. The spread of this disease is influenced by mobility and environmental conditions that support the breeding of the Aedes Aegypti mosquito. The community service team focused on three main objectives in this activity by providing education about the dangers of DBD, teaching how to prevent the spread of mosquitoes, and using aromatherapy candles to prevent mosquitoes. The purpose of the counseling is to reduce diseases caused by mosquitoes by teaching the community about how to live a healthy life.Used cooking oil processed into aromatherapy candles is one of the new innovations in preventing DBD. This method is considered practical and easy to implement by the community by utilizing materials available around them. The community is also educated on how to maintain environmental cleanliness, such as draining and closing water reservoirs regularly and recycling household waste to reduce the possibility of mosquito breeding grounds. The hope is that this outreach will make the community more independent in maintaining environmental health and actively involved in preventing dengue fever so that the risk of increasing cases in their village can be reduced. This activity has succeeded in achieving the stated objectives, namely increasing community awareness and involvement in preventing dengue fever.